Self-rated health and all-cause and cause-specific mortality of older adults: Individual data meta-analysis of prospective cohort studies in the CHANCES Consortium - Bamia, Christina; Orfanos, Philippos; Juerges, Hendrik; Schöttker, Ben; Brenner, Hermann; Lorbeer, Roberto; Aadahl, Mette; Matthews, Charles E.; Klinaki, Eleni; Katsoulis, Michael; Lagiou, Pagona; Bueno-de-mesquita, H.B(as).; et al. (Maturitas, 2017)
•The association of self-rated health with mortality is confirmed by the large CHANCES study.•Self-rated health is a simple tool that may be used to identify elders at risk of early mortality.•Changing factors related to self-rated health is important for the elders to feel and be healthy. To evaluate, among the elderly, the association of self-rated health (SRH) with mortality, and to identify determinants of self-rating health as “at-least-good”. Individual data on SRH and important covariates were obtained for 424,791 European and United States residents, ≥60 years at recruitment (1982–2008), in eight prospective studies in the Consortium on Health and Ageing: Network of Cohorts in Europe and the United States (CHANCES). In each study, adjusted mortality ratios (hazard ratios, HRs) in relation to SRH were calculated and subsequently combined with random-effect meta-analyses. All-cause, cardiovascular and cancer mortality. Within the median 12.5 years of follow-up, 93,014 (22%) deaths occurred. SRH “fair” or “poor” vs. “at-least-good” was associated with increased mortality: HRs 1.46 (95% CI 1·23–1.74) and 2.31 (1.79–2.99), respectively. These associations were evident: for cardiovascular and, to a lesser extent, cancer mortality, and within-study, within-subgroup analyses. Accounting for lifestyle, sociodemographic, somatometric factors and, subsequently, for medical history explained only a modest amount of the unadjusted associations. Factors favourably associated with SRH were: sex (males), age (younger-old), education (high), marital status (married/cohabiting), physical activity (active), body mass index (non-obese), alcohol consumption (low to moderate) and previous morbidity (absence). SRH provides a quick and simple tool for assessing health and identifying groups of elders at risk of early mortality that may be useful also in clinical settings. Modifying determinants of favourably rating health, e.g. by increasing physical activity and/or by eliminating obesity, may be important for older adults to “feel healthy” and “be healthy”.